ELECTRONIC STRUCTURE OF LAYERED COMPOUNDS WHICH CONSISTS OF TWO- AND TRICOORDINATED CARBON ATOMS - T.E. Belenkova; V.M. Chernov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
In this paper the electronic structure of five major structural modification of graphyne: α-, β1-, β2-, γ1- and γ2- graphyne were calculated by method of density functional theory.